Pengaruh Pengadukan pada Proses Pelapisan Ni-TiAlN Menggunakan Teknik Elektrodeposisi untuk Perlindungan Bahan Tungsten Karbida Terhadap Korosi - Ade Lina Permatasari; Esmar Budi; Agus Setyo Budi (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
The research of electrodeposited Ni-TiAlN nanocomposite thin film on tungsten carbide rod as substrate has been investigated. The purpose of this study was to determine the influence of agitation speed in formation of morphology and corrosion resistance. Solution of agitation speed when electrodeposited process at low speed agitation 600r/min, medium speed agitation 900r/min dan high speed agitation 1200r/min. Electrodeposited process was performed at current 3 mA for about 15 minutes. Amount of 6 gr/L of TiN and AlN powders were added into electrolyte solution consist of 0.38 M Ni2SO4.6H2O, 0.17 M NiCl2. 6H2O, 0.49 M H3BO3 and 0.01 gram of Sodium Dodecyl Sulfate. The results show that the nanocomposite thin film morphology is different in each agitation speed. Keywords: Ni-TiAlN nanocomposite film, electrodeposition, agitation, electrolyte solution.